Net water uptake, a neuroimaging marker of early brain edema, as a predictor of symptomatic intracranial hemorrhage after acute ischemic stroke - Xu, Tianqi; Yang, Jianhong; Han, Qing; Wu, Yuefei; Gao, Xiang; Xu, Yao; Huang, Yi; Wang, Aiju; Parsons, Mark W.; Lin, Longting (Frontiers in Neurology, 2022)
Objective: We hypothesized that quantitative net water uptake (NWU), a novel neuroimaging marker of early brain edema, can predict symptomatic intracranial hemorrhage (sICH) after acute ischemic stroke (AIS). Methods: We enrolled AIS patients who completed admission multimodal computed tomography (CT) within 24 hours after stroke onset. NWU within ischemic core and penumbra were calculated based on admission CT, namely NWU-core and NWU-penumbra. sICH was defined as the presence of ICH in the infarct area within 7 days after stroke onset, accompanied by clinical deterioration. The predictive value of NWU-core and NWU-penumbra on sICH was evaluated by logistic regression analyses and receiver operating characteristic (ROC) curve. A pure neuroimaging prediction model was built considering imaging markers have the potential to be automatically quantified with artificial algorithm on image workstation. Results: 154 patients were included, of which 93 underwent mechanical thrombectomy (MT). The median time from symptom onset to admission CT was 262 min (interquartile range, 198 to 368). In patients with MT, NWU-penumbra (OR =1.442; 95% CI = 1.177 - 1.766; P < 0.001) and NWU-core (OR = 1.155; 95% CI = 1.027 - 1.299; P = 0.016) were independently associated with sICH with adjustments for age, sex, time from symptom onset to CT, hypertension, lesion volume and admission National Institutes of Health Stroke Scale (NIHSS) score. ROC curve showed that NWU-penumbra had better predictive performance than NWU-core on sICH (area under the curve (AUC): 0.773 vs 0.673). The diagnostic efficiency of predictive model was improved with the containing of NWU-penumbra (AUC: 0.853 vs 0.760). Pure imaging model also presented stable predictive power (AUC= 0.812). In patients without MT, however, only admission NIHSS score (OR = 1.440; 95% CI = 1.055 - 1.965; P = 0.022) showed significance in predicting sICH in multivariate analyses. Conclusions: NWU-penumbra may have better predictive performance than NWU-core on sICH after MT. Pure imaging model showed potential value to automatically screen patients with sICH risk by image recognition, which may optimize treatment strategy.